Prevalensi, Intensitas, dan Dominansi Parasit pada Ikan Manggabai (Glossogobius giuris) di Danau Limboto Provinsi Gorontalo - Hamid, Alia; Lamondo, Djuna; Aydalina, Regina Valentine (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aimed to identify the different types of parasites infecting manggabai fish (Glossogobius giurus) in Lake Limboto, in addition to analyzing the intensity, prevalence, and dominance of parasites in the population. Twenty manggabai fish samples were collected from three different locations in Lake Limboto, namely Dembe 1, Tabmela, and Hutuo. The parasite examination process was carried out at the Zoology Laboratory of the Biology Department of Gorontalo State University, focusing on organs such as skin, gills, fins, and digestive organs. The method applied was the native method, which involves direct observation. The identification results showed the presence of three types of parasites in manggabai fish, namelyÂ GyrodactylusÂ sp.,Â CamallanusÂ sp., andÂ Ligula intestinalis. The highest prevalence was recorded forÂ GyrodactylusÂ sp. at 65%, indicating a significant spread of parasites in the fish population. The parasite intensity of CamallanusÂ sp. from Hutuo at 7. The parasiteÂ Ligula intestinalisÂ showed the highest dominance with a value of 44%. Meanwhile, the highest prevalence and intensity values were placed in the frequent and mild categories.